Crescimento e desempenho de bertalha (Basella alba L.) em função do tipo de propagação - da Silva Campos, Rene Arnoux; Lima, Giuseppina Pace Pereira [UNESP]; Seabra Junior, Santino; Suekane Takata, William Hiroshi [UNESP]; da Silva, Ewerton Gasparetto [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2012)
Malabar spinach is a non-conventional vegetable propagated mainly by seeds. This research evaluated the propagation by stem cuttings as an alternative method of propagation and verified its effect on growth of the vegetable. Plantlets propagated by seeds and stem cuttings were grown in greenhouse and their growth were evaluated in five successive intervals of 21 days each, with the first evaluation carried out 60 days after the transplanting. The results showed that the propagation methods have influence on the Malabar spinach growth. Plants propagated by seeds display slow, but vigorous growth, with larger relative yield of leaves and tender leaves, while plants propagated by cuttings showed fast initial growth, with rapid fruit formation. Thus, the propagation by cuttings is more suitable for seed production, while propagation by seeds is more profitable for leaves production.

A bertalha é uma hortaliça não-convencional propagada principalmente por sementes. Nesse estudo avaliou-se a estaquia como método alternativo de propagação e seu efeito no crescimento da hortaliça. Mudas produzidas por sementes e estaquia foram cultivadas em casa de vegetação. O crescimento e o desempenho foram avaliados em cinco intervalos sucessivos de 21 dias, sendo a primeira amostragem realizada 60 dias após o transplantio. Os resultados mostraram que os métodos de propagação influenciaram o crescimento e a produtividade de bertalha. As plantas propagadas por sementes apresentaram crescimento mais lento e mais vigoroso, com maior produção relativa de folhas e folhas mais espessas. Já as plantas propagadas por estaquia apresentaram rápido crescimento inicial, com rápida formação de frutos. A estaquia é mais adequada à produção de sementes, enquanto a propagação por sementes é mais vantajosa para a produção de folhas.
Growth and yield of malabar spinach (Basella alba L.) in relation to the propagation method
Keywords: Non-conventional vegetable; Cuttings; Seeds